Aspidosperma excelsum and its pharmacological potential: in silico studies of pharmacokinetic prediction, toxicological and biological activity (Research, Society and Development, 2020)
Based on ethnobotanical studies, the Aspidosperma excelsum was selected due to its highest claim of popular use for malaria and febrile diseases treatments. This species is rich in secondary metabolites as alkaloids and therefore, the aim of this study was to evaluate the pharmacokinetic, toxicological and biological activity of alkaloids isolated from Aspidosperma excelsum by in silico studies. All substances already isolated from this species were submitted to predictive studies of biological, toxicological and pharmacokinetic activities. Predictive studies of biological activities did not attribute the antimalarial activity to pure substances. However, other activities were found, such as: action on central nervous system and antineoplastic activity. In pharmacokinetic terms, many substances showed an inhibitory action on cytochrome P450 (CYP) and many adverse reactions, highlighting actions on the CNS. Also, several alkaloids, being nitrogenous substances, presented mutagenic or genotoxic activities. Thus, it is demonstrated the species potential for biological activities not yet studied, as well as the importance of investigating its pharmacokinetic and toxicological properties, justifying the accomplishment of the present study.